Daily planet [videorecording]: in search of mount everest - Discovery Channel (Quezon City : Magna Vision, 2005)
Climb Mt. Everest for a look at the trials and triumphs involved in reaching the summit. Visit base camp to learn about preparing for the trek. Find out why nearly Everest expeditions rely on Sherpas, support climbers. And discover why these Nepalese climbers are so well suited for high-altitude living.
Keywords: Sherpa (Nepalese people).; Mountaneering -- Everest, Mount (China and Nepal).